Financial Risk Assessment in PPP Projects for Affordable Housing - Yanti, Sonia Indah Nor; Rachmawati, Farida (Borong Newinera Publisher, 2025)
This study aims to identify and evaluate risk related to financial in Public-Private Partnership projects specifically on affordable housing sector in Indonesia. The research was conducted using a qualitative-descriptive approach supported by a structured questionnaire survey distributed to government and private sector stakeholders. The assessment method applied is the Probability-Impact Matrix, which enables systematic evaluation of each risk based on its likelihood of occurrence and its potential impact on project performance. The results indicate that land provision and dependence on public funding are the most significant financial risks, categorized as high and very high levels. Other identified risks include credit and loan availability, construction cost fluctuations, and investment funding stability, all of which pose varying degrees of concern. The study also highlights the importance of experience, position, and educational background of the respondents in providing comprehensive insights into risk perception. The findings conclude that proactive financial risk mitigation, including appropriate cost-sharing mechanisms and contingency planning, is crucial for the sustainability of affordable housing PPP projects. This research offers valuable input for policymakers and private stakeholders in designing more resilient financing strategies for future infrastructure development.